The Effect of CYP1A1 and GSTP1 Isozymes on the Occurrence of Aortic Aneurysms - Simsek, Erdal; Kilic, Murat; Simsek, Gulcin; Oguztuzun, Serpil; Moran, Busra; Saritas, Ahmet; Ulus, A. Tulga (The Thoracic and Cardiovascular Surgeon, 2015)
Background Aortic aneurysms are vascular diseases that are associated with high mortality and morbidity. Cytochrome P450 CYP1A1 and glutathione S-transferase (GSTP1) isozymes were searched and compared with the patients who had experienced aortic surgery due to aortic aneurysm and atherosclerotic patients without aneurysm to find the relation of the oxidative stress with the aneurysms.Materials and Methods Study group consisted of the patients with the diagnosis of aortic aneurysm (group I, n: 12) and control group who were operated for coronary bypass surgery: preoperatively drug users (group II, n: 21) and nonusers (group III, n: 15). Paraffin sections (4 μm thick) of aortic biopsy materials were stained with hematoxylin and eosine, CYP1A1 and GSTP1 immunohistochemical markers. The specimens were evaluated using light microscopy at 40- to 400-fold magnification.Results The expressions of CYP1A1 and GSTP1 isozymes were found statistically significantly higher in the patients who have an aortic aneurysm than both the control groups (p < 0.05). There was no significant association between protein expressions, drugs and duration of usage, patient's demographic variables, and smoking (p > 0.05).Conclusions In this pioneering study, CYP1A1 and GSTP1 isozymes are related with the aneurysms. The strategy that prevents the oxidative stress for the patients who had aortic aneurysms could be a valuable choice of searching to effect the aneurysmal progression.
Keywords: aortic aneurysm; aorta/aortic; artery/arteries; coronary bypass surgery; CYP1A1; GSTP1; vascular disease